Inputs to Improve Health Service Delivery: Evidence from Selected Municipalities in Leyte, Philippines - Miguel E. Mangada (Medicine and Medical Research: New Perspectives Vol. 1, 2024)
Gleaning from the theoretical views cited, a conceptual framework was developed that sheds light on the scope of the study. The conceptual paradigm indicates that this study will investigate specific areas provided by the local government health units and the extent of health service delivery involving two health concerns. Quantitative data gathered from different research instruments was corroborated by qualitative data gathered from the interviews and focus group discussions, documentary analysis, and questionnaires. This study sheds light on the strengths and gaps in health service delivery in selected municipalities in Leyte, providing valuable insights for improving overall health outcomes in the region.